Republic of Armenia : Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility. (IMF Staff Country Reports; Country Report, 2005)
This paper assesses Armenia's Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF). Under the previous PRGF-supported program, Armenia accomplished macroeconomic stability, rapid growth, and a significant reduction in poverty. To consolidate these gains, there is a need to address the remaining structural weaknesses and implementation gaps as identified in the ex post assessment of Armenia's long-term IMF engagement. The 2005 reform agenda is ambitious and focuses on fiscal and financial sector reforms. Armenia's economic outlook is favorable, although not without risks.